PKM bagi Guru IPA Fisika se-Kabupaten Maros - Muhammad Arsyad; Helmi Helmi; Khaeruddin Khaeruddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM activities carried out aim to answer the formulation of the problems, namely: (1) To design karst-based physics learning using the Student Worksheet (LKPD) (2) To Design the use of Learners (LKPD) in learning Physics Science. (3) To analyze the responses of Basic Physical Science Teachers in the implementation of PKM Activities. The method in PKM activities is in the form of problem solving which in principle is how to create and design a karst area environment as a learning resource supplemented with Student Work Sheets (LKPD). The form of problem solving offered is to provide guidance to Physics Science Teachers, in designing karst areas as a source of learning and designing LKPD in accordance with the ability of teachers at each level of the class. Some variations of the training methods are: (1) the experimental method (2) the discussion method (3) the lecture method. The results of Community Service activities obtained 1) Design of Physical Science Learning Based on Karst with Student Worksheets (LKPD) 2) The Use of Student Worksheets (LKPD) in Physics Science Learning, 79.17%, participants agreed to design karst-based learning using LKPD, 75.0% of the participants agreed to conduct experiments and prepare LKPD based on karst area, 62.50% of participants would conduct dissemination activities for other subject teachers, 66.67% of participants would give assignments to students by observing directly in Karst Areas Maros, 70.83% of participants will include this activity as a routine MGMP activity every year, 95.83% of Teachers are able to carry out karst-based Physics Learning with LKPD.